Expressions and Distributions of Leucine-enkephalin, Delta, Mu, and Kappa Opioid Receptors in Four Systems of the Octopus, Octopus ocellatus by Comparative Immunohistochemical Method and ELISA - SHA, AI; HAO, HY (Journal of the Hellenic Veterinary Medical Society, 2022)
We have investigated the expressions and distributions of leucine-enkephalin (Leu-enk), delta (δ), mu (μ), and kappa (κ) opioid receptors immunoreactivities in the respiratory, circulatory, excretory and reproductive systems of the Octopus, Octopus ocellatus, by comparative immunohistochemical method and enzyme-linked immunosorbent assay (ELISA). The results showed that δ opioid receptor and Leu-enk immunoreactivities were both detected in the branchia, ventricle, branchial heart, ovary and oviducal gland, while δ opioid receptor was additionally detected in the branchial gland and kidneys in less extend. The majority of the examined tissues presented weak immunoreactivities of δ opioid receptor and Leu-enk, with the notable exception of the white body and spermary tissues that were found negative. No labellings of μ and κ opioid receptors were observed in the respiratory, circulatory, excretory and reproductive systems of O. ocellatus. The combined results of δ opioid receptor and Leu-enk immunoreactivities indicated that they may be involved in the regulations of respiration, circulation, reproduction and endocrine together with other hormones or neurotransmitters in the O. ocellatus’ body. The different densities of δ opioid receptor and Leu-enk in the respiratory, circulatory, excretory and reproductive systems of O. ocellatus may be related to the different functions.